2016
DOI: 10.1016/j.carbpol.2016.06.081
|View full text |Cite
|
Sign up to set email alerts
|

Edible films based on cassava starch and fructooligosaccharides produced by Bacillus subtilis natto CCT 7712

Abstract: The objectives of this work were to produce fructooligosaccharides (FOSs) by using the microorganism Bacillus subtilis natto CCT 7712 and to employ these FOSs as a functional ingredient in cassava starch edible films, which were characterized according to their microstructure, mechanical and barrier properties. The produced FOSs could be easily dissolved, resulting in homogeneous filmogenic solutions, which were easily manipulated to obtain films by casting. FOSs were added in different concentrations (0, 1, 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
14
2
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 31 publications
6
14
2
4
Order By: Relevance
“…The addition of probiotic and/or FOS (mainly the latter) made the films more permeable to water vapor, as previously reported from the presence of other bacteria (Ebrahimi et al, 2018;Sánchez-González, Saavedra, & Chiralt, 2013) or prebiotic oligosaccharides (Orozco-Parra et al, 2020), which is ascribed to disruptions on the polymeric structure of the films, as already mentioned for tensile properties. In contrast to this study, Bersaneti et al (2016) reported that FOS decreased the WVP of starch films, which the authors ascribed to lowering effects on water diffusivity through the matrix; on the other hand, those authors (as well as Orozo-Parra et al, 2020) reported that FOS increased the water solubility of the films, due to their hydrophilic character. Since permeability is defined as the product of diffusivity and solubility, one mechanism seems to have dominated the WVP results in the study by Bersaneti et al (2016), and the other to have dominated WVP in the present study as well in the one by Orozco-Parra et al (2020).…”
Section: Physical Properties Of Filmscontrasting
confidence: 82%
See 1 more Smart Citation
“…The addition of probiotic and/or FOS (mainly the latter) made the films more permeable to water vapor, as previously reported from the presence of other bacteria (Ebrahimi et al, 2018;Sánchez-González, Saavedra, & Chiralt, 2013) or prebiotic oligosaccharides (Orozco-Parra et al, 2020), which is ascribed to disruptions on the polymeric structure of the films, as already mentioned for tensile properties. In contrast to this study, Bersaneti et al (2016) reported that FOS decreased the WVP of starch films, which the authors ascribed to lowering effects on water diffusivity through the matrix; on the other hand, those authors (as well as Orozo-Parra et al, 2020) reported that FOS increased the water solubility of the films, due to their hydrophilic character. Since permeability is defined as the product of diffusivity and solubility, one mechanism seems to have dominated the WVP results in the study by Bersaneti et al (2016), and the other to have dominated WVP in the present study as well in the one by Orozco-Parra et al (2020).…”
Section: Physical Properties Of Filmscontrasting
confidence: 82%
“…The decreased strength was expected due to the low glass transition temperature (T g ) of FOS (Rajam & Anandharamakrishnan, 2015), related to the plasticizing effects of FOS, as previously reported in starch (Bersaneti, Mantovan, Magri, Mali, & Celligoi, 2016), methylcellulose (Romano et al, 2014), and whey protein films (Fernandes et al, 2020), meaning that FOS interfered with the hydrogen bonds among hydroxyl groups of the matrix (Romano et al, 2014). The impaired elongation found in this study as resulting from FOS addition corroborates results by Karimi et al (2020) with polydextrose in films, but contrasts with those reported by other authors from FOS or other oligosaccharides (Bersaneti et al, 2016;Fernandes et al, 2020;Orozco-Parra, Mejía, & Villa, 2020), and suggests that the interaction of FOS with the matrix was probably very poor, weakening the matrix-FOS interface.…”
Section: Physical Properties Of Filmssupporting
confidence: 79%
“…A typical composition of the cassava root is moisture (70%), starch (24%), fiber (2%), protein (1%), and other substances including minerals (3%) (Tonukari 2004). Cassava starch extracted from the cassava root and has been used in edible bioplastic production (Bersaneti et al 2016;Piñeros-Hernandez et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…En consecuencia, la red polimérica se torna menos densa, mejorando así la extensibilidad y la flexibilidad (Liu et al, 2006;Martelli, 2006 ). Bersaneti et al, (2016) incluyeron FOS en la formulación de películas de almidón de cassava. En este sistema, la adición de FOS disminuyó la T g de las películas, siendo los valores obtenidos tanto más bajos cuanto mayor era la concentración de FOS.…”
Section: I12 Películas Comestibles De Metilcelulosa Como Recubrimunclassified
“…Las propiedades estructurales y mecánicas de películas de metilcelulosa han sido estudiadas recientemente (Tavera-Quiroz et al, 2013). Asimismo, han sido desarrolladas películas comestibles a partir de FOS (Ramesh & Siddalingaiya, 2006;Angiolillo et al, 2014;Bersaneti et al, 2016). Sin embargo, la incorporación de FOS en películas de metilcelulosa como protectores de microorganismos sensibles da lugar a nuevos tipos de películas cuyas propiedades físico-químicas deben ser cuidadosamente analizadas.…”
Section: I13 Uso De Sustancias Protectoras En Películas Cargadas unclassified